Evaluation of fully-functionalized diazirine tags for chemical proteomic applications. Issue 22 (7th May 2021) - Conway, Louis P.; Jadhav, Appaso M.; Homan, Rick A.; Li, Weichao; Rubiano, Juanita Sanchez; Hawkins, Richard; Lawrence, R. Michael; Parker, Christopher G.
Abstract : The chemical proteomic properties of five diazirine-based, fully-functionalized photoaffinity tags, including a newly developed, minimal tag, were compared. This study provides guidance for the development of new photoaffinity probes. Abstract : The use of photo-affinity reagents for the mapping of noncovalent small molecule–protein interactions has become widespread. Recently, several 'fully-functionalized' (FF) chemical tags have been developed wherein a photoactivatable capture group, an enrichment handle, and a functional group for synthetic conjugation to a molecule of interest are integrated into a single modular tag. Diazirine-based FF tags in particular are increasingly employed in chemical proteomic investigations; however, despite routine usage, their relative utility has not been established. Here, we systematically evaluate several diazirine-containing FF tags, including a terminal diazirine analog developed herein, for chemical proteomic investigations. Specifically, we compared the general reactivity of five diazirine tags and assessed their impact on the profiles of various small molecules, including fragments and known inhibitors revealing that such tags can have profound effects on the proteomic profiles of chemical probes. Our findings should be informative for chemical probe design, photo-affinity reagent development, and chemical proteomic investigations.